(untitled) (Journal of Oriental Studies, 2016)
The issue of borrowing terms from language A in the Arabic language is considered by some researchers, including from the Arab world. In Arabic terminology borrowing is studied as «التعريب» (lit.. Arabization), which is divided into two kinds «دخيل» and «معرب» depending on the degree of change in the lexical units. In this article the complex classification of borrowing will be considered which resulted in its most effective identified sub methods of term formation of computer science.